A COMPARATIVE STUDY OF INHIBITORS EFFICIENCY ON CORROSION OF CARBON STEEL REBAR IN CHLORIDE ENVIRONMENT - NACHIAPPAN, ROHAN (IRC, 2021)
The rebar’s function in reinforced concrete structures is to provide strength and hold the concrete in tension.